BEYOND ENTERTAINMENT: EXPLORING THE SOCIAL, RELIGIOUS, AND CULTURAL SIGNIFICANCE OF THARU DANCE TRADITIONS - Singh, Aman; Mahata, Animesh (ShodhKosh: Journal of Visual and Performing Arts, 2026)
This paper presents a comprehensive study of the traditional folk dances of the Tharu tribe residing in the Indian state of Bihar (especially the Champaran region) and the Terai region of Nepal. The study has made an in-depth analysis of distinct dance styles including Jhumra, Dhumaria, Sakia, Holi, Magahi, Khelwa, Devi Nritya, which are integral parts of the cultural identity of the Tharu community. The research findings show that these dances are not just a means of entertainment, but are a powerful expression of community unity, religious faith, nature worship and collective rituals related to the seasonal cycle. In particular, Jhumra dance is a symbol of collective gaiety, while Devi Nritya reflects religious-spiritual beliefs. At present, this rich cultural heritage is endangered due to globalization, urban migration, and modern education system and changing interests of the younger generation. The study used mixed methods to collect primary data from 150 participants (senior artists, younger generation and cultural experts), as well as analyze secondary material from various museums, libraries and archives. At the end of the research, 15 practical suggestions have been presented for the preservation and promotion of Tharu dance traditions, which include inclusion in school curriculum, promotion of cultural tourism, government grant schemes, measures to increase community participation and digital documentation. This study presents an important contribution towards the preservation of tribal cultural heritage.